2016
DOI: 10.1111/tan.12737
|View full text |Cite
|
Sign up to set email alerts
|

What is wrong with the regulatory T cells and foetomaternal tolerance in women with recurrent miscarriages?

Abstract: Couples of whom the woman has had a miscarriage have two major concerns: the cause and possible risk of recurrence. Unfortunately, a significant proportion of cases of recurrent miscarriage (RM) remain unexplained despite detailed investigation. Because data suggest that regulatory T cells (Treg) are involved in the maternal acceptance of the allogeneic foetus, RM could possibly be explained by a disturbance of the Treg network. The possible role of Tregs in RM is described in this review, as well as their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 112 publications
(152 reference statements)
1
6
1
Order By: Relevance
“…The higher frequency of CD127 − CD25 ++ cells (Treg) in colostrum that was demonstrated in this study may support a form of passive tolerogenic immunity mediated by memory cells. Increased numbers and functionality of Treg cells are essential to maintain a pregnancy . Blood may be a source of colostrum Treg cells during puerperium; however, we did not observe an association between both compartments (Spearman's approximation = 0.058, P = .394).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The higher frequency of CD127 − CD25 ++ cells (Treg) in colostrum that was demonstrated in this study may support a form of passive tolerogenic immunity mediated by memory cells. Increased numbers and functionality of Treg cells are essential to maintain a pregnancy . Blood may be a source of colostrum Treg cells during puerperium; however, we did not observe an association between both compartments (Spearman's approximation = 0.058, P = .394).…”
Section: Discussioncontrasting
confidence: 81%
“…Treg cells’ regulatory properties involve the inhibition of effector T and antigen‐presenting cells by scavenging interleukin (IL)‐2 by CD25; inhibitory signals mediated by cell‐to‐cell contact with surface molecules, such as cytotoxic T‐lymphocyte antigen (CTLA‐4 or CD152) and programmed cell death‐1 (PD‐1 or CD279); and secretion of suppressive cytokines, such as transforming growth factor (TGF)‐β or IL‐10 . In pregnancy, increased numbers and functionality of these cells are essential for establishing and maintaining the semiallogeneic fetus; by contrast, quantitative/qualitative alterations of Treg cells are associated with miscarriage and pregnancy complications, such as preeclampsia . It is also possible that the adoptive transfer of Treg provides tolerance to an antigenically unproven host, such as the newborn …”
Section: Introductionmentioning
confidence: 99%
“…50 An efficacy of vitamin D interventional strategies trial showed that oral supplementation is the best vitamin D supplementation strategy in adults and children. 54 In a recent study, researchers have tried conditions. 54 In a recent study, researchers have tried conditions.…”
Section: Discussionmentioning
confidence: 99%
“…17,53 Previous studies highlight that Treg cells were decreased in patients with RPL compared with in women with normal early pregnancy, and that they were at a level comparable with that of non-pregnant controls. 54 In a recent study, researchers have tried Treg cells as a therapy for RPL. Additionally, low levels of vitamin D may reduce the number of Treg cells in circulation, disrupt immune system homeostasis and increase inflammatory activity in psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of regulatory cells at the maternal–fetal interface is crucial in mammals with invasive placentation (4). A potential dysregulation of regulatory cells may have several consequences on the human health and has been associated with autoimmune diseases, cancer, chronic infections (5, 6), and pregnancy-related disorders, including preterm birth, preeclampsia, and recurrent pregnancy loss (710). CD4 + CD25 + regulatory T cells and CD19 + CD24 hi CD27 + regulatory B cells are increased during normal pregnancies, while some cases of pregnancy loss associate with a lack of this increment (8, 11).…”
Section: Introductionmentioning
confidence: 99%